THE INFLUENCE OF SERVICE, PRICE, AND ADVERTISING ON SHOPEE PURCHASE DECISIONS - Michael; Ivonie; Angeliou, Ryan; Kozen, Vincent; Butar Butar , Mangasi; Gultom, Robinhot (Mount Hope Economic Global Journal, 2025)
Currently, the development of the business world in online shops is increasing and people are also helped by the existence of online shops where people as consumers do not need to visit the shop to shop. This study aims to test the Influence of Service, Price and Advertising on Purchasing Decisions on Shopee. Research focuses on quantitative data, tends to use associative research. The population was 237 consumers who visited the Shopee application and the sampling technique was Slovin. The research sample consisted of 149 consumers. The results of the study are that service has a positive influence on purchasing decisions on Shopee. Price has a positive influence on purchasing decisions on Shopee. Advertisements have a negative influence on purchasing decisions on Shopee. Service_X1, Price X2 and Advertising X3 influence Purchasing Decisions (Y) on Shopee.